Better tests of consciousness are needed, but skepticism about unconscious processes is unwarranted. Issue 1 (24th January 2014) - Ogilvie, Ryan; Carruthers, Peter
Abstract What people report is, at times, the best evidence we have for what they experience. Newell & Shanks (N&S) do a service for debates regarding the role of unconscious influences on decision making by offering some sound methodological recommendations. We doubt, however, that those recommendations go far enough. For even if people have knowledge of the factors that influence their decisions, it does not follow that such knowledge is conscious, and plays a causal role, at the time the decision is made. Moreover, N&S fail to demonstrate that unconscious thought plays no role at all in decision making. Indeed, such a claim is quite implausible. In making these points we comment on their discussion of the literature on expertise acquisition and the Iowa Gambling Task.